Considerations for an In Vitro, Cell-Based Testing Platform for Detection of Adverse Drug-Induced Inotropic Effects in Early Drug Development. Part 1: General Considerations for Development of Novel Testing Platforms - Guth, Brian D.; Engwall, Michael; Eldridge, Sandy; Foley, C. Michael; Guo, Liang; Gintant, Gary; Koerner, John; Parish, Stanley T.; Pierson, Jennifer B.; Ribeiro, Alexandre J. S.; Zabka, Tanja; Chaudhary, Khuram W.; et al. (Frontiers in Pharmacology, 2019)
Drug-induced effects on cardiac contractility can be assessed through the measurement of the maximal rate of pressure increase in the left ventricle (LVdP/dtmax) in conscious animals and such studies are often conducted at the late stage of preclinical drug development. Detection of such effects earlier in drug research using simpler, in vitro test systems would be a valuable addition to our strategies for identifying the best possible drug development candidates. Thus, testing platforms with reasonably high throughput and affordable costs would be helpful for early screening purposes. There may also be utility for testing platforms that provide mechanistic information about how a given drug affects cardiac contractility. Finally, there could be in vitro testing platforms that ultimately could contribute to the regulatory safety package of a new drug. The characteristics needed for a successful cell or tissue-based testing platform for cardiac contractility will be dictated by its intended use. In this article, general considerations are presented with the intent of guiding the development of new testing platforms that will find utility in drug research and development. In the following article (Part 2), specific aspects of using human induced stem cell-derived cardiomyocytes for this purpose are addressed.